Efeitos da restrição de tiamina e da gestação, em fêmeas Wistar, sobre os níveis periféricos e centrais de tiamina e derivados fosforilados, BDNF e aspectos comportamentais - Polliana Toledo Nunes (2012)
The purposes of the present study were to verify the effects of thiamine (vitamin B1) restriction and pregnancy on the central and peripheral levels of thiamine and its derivatives, neurotrophin BDNF and behavioral aspects. Several authors have shown that thiamine deficiency causes lesions in different brain regions and affects central neurochemical circuits, which are related to various aspects of behavior. Researchers have also used the model of thiamine deficiency in pregnant rats and/or lactating rats, in order to verify the effects on neurobiological and behavioral aspects, in the offspring. However, as far as we know, there is only one study conducted in 1965, in which the authors used an experimental model to evaluate the effects of the thiamine deficiency on pregnant rats. Thus, as a first step to characterize a rat model of maternal restriction of thiamine, the aim of the present study were to assess biochemical changes - levels of thiamine and its derivatives and BDNF in the blood and brain areas - and cognitive and emotional aspects of the experimental subjects. Seventy two females rats, three months old, were divided into four subgroups: Standard Pregnant rats (n = 18), Standard Non-Pregnant rats (n = 18), Thiamine-Restricted Pregnant rats (n = 18) and Thiamine-Restricted Non-Pregnant rats (n = 18). Following the rats from each of these groups were subdivided according to three distinct periods in relation to the pregnancy process (period 1: 1st week; Period 2: 1st and 2nd weeks and Period 3: 1st, 2nd and 3rd weeks). Animals from each group were submitted to behavioral tests, to evaluate emotional and cognitive aspects, in the elevated T maze. After the behavioral tests the animals were killed and peripheral samples (blood and plasma) and brain areas (thalamus and hippocampus) were collected for thiamine and its derivatives analysis by High Performance Liquid Chromatography and BDNF immunassay by ELISA. Thiamine restriction affects weight gain only in the period corresponding to the 3rd week of pregnancy. In addition, the effects of this restriction on food consumption were more pronounced in pregnant rats than in non-pregnant rats. The rats of all groups were able to learn the inhibitory avoidance task and succeeded to retrieve the information acquired 72 hours before. In conclusion, the data show that subclinical thiamine deficiency in pregnant rats interferes, mainly in the late-stage of pregnancy, with the feeding behavior, biochemical parameters (levels of thiamine and its derivatives and BDNF) in the dams blood and brain regions. In addition, the present results show that a subclinical thiamine restriction adversely affects the development of the fetus.